The Language Warriors: Transcending ideologies on bilingualism in education. Issue 1 (March 2023) - Alonso, Lara; Le, Khanh
This article explores how middle school youth view bilingualism and act on these views to transform their school and their communities. Following a post-structuralist perspective on language and society, a lens from raciolinguistic ideologies, and a creative justice approach, we developed a Participatory Action Research project in which seventh and eighth grade students became co-researchers as we explored how to make bilingualism more welcome in their school. In this paper, we reveal how bilingualism became a way to unite students and to fight deficit views of language minoritized communities. We show the students' potential to engage in critical thinking about bilingualism and to become agents in their schools and communities. Our findings informed the school on how to acknowledge and leverage the students' language practices and lived experiences based on a framework of armed and bilingual love.